Spatial distribution of Aphis craccivora Koch 1854 (Hemiptera: Aphididae) in cowpea (Vigna unguiculata (L.) Walp.) (Research, Society and Development, 2020)
The determination of the type of spatial distribution of the insect-pest is the first step to establish a sampling plan, therefore the objective of this work was to study the spatial distribution of A craccivora in cowpea. The studies were developed during the period of cultivation of cowpea "from the drought" at the experimental farm of the Universidade Estadual de Mato Grosso do Sul (UEMS), in Aquidauana-MS. The 300 m2 experimental area was formed by 40 plots of four lines with 5 meters in length, spaced 0.50 meters apart, considering the two central lines as useful area. Sampling was performed weekly from the appearance of the first aphid. The average variance and the aggregation indexes were determined. The Poisson distribution, negative binomial distribution and positive binomial distribution were used to describe the theoretical frequency distribution for the population samples: The sampling variances were always higher than the average, which indicates adjustment to the negative binomial distribution, with the insect tending to aggregate, which normally occurs in the field for the Indices of Variance-Average Ratio (I), Morisite Index (Iδ) and Exponent k of the Negative Binomial Distribution (k), was obtained for the distribution of the population of black aphids in cowpea culture, the distribution in aggregate format. For the frequency distribution tests, the most suitable for the samples was the Negative Binomial distribution, indicating the population of black aphids behave in an aggregate manner in the cowpea culture.